Denmark Vesey's Bible the thwarted revolt that put slavery and scripture on trial - Schipper, Jeremy 1975- (Princeton Princeton University Press, 2022)
Cover -- Contents -- List of Illustrations -- List of Major Figures -- Timeline of Major Events -- Preface -- Acknowledgments -- Introduction. Crimes of the Blackest Hue -- Chapter One. He Shall Surely Be Put to Death -- Chapter Two. By the Mouth of Witnesses -- Chapter Three. With Fear and Trembling -- Chapter Four. Now Profitable -- Chapter Five. They Shall Be Your Bondmen Forever -- Chapter Six. For He Is His Money -- Epilogue. No Respecter of Persons -- Appendix -- Notes -- Bibliography -- Image Credits -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Bible-Black interpretations; Slavery and the church; Charleston (S.C.)-History-Slave Insurrection, 1822; Electronic books